The Preparation and Identification of Characteristic Flavour Compounds of Maillard Reaction Products of Protein Hydrolysate from Grass Carp (Ctenopharyngodon idella) Bone - Yunliang Li; Xiaojing Wang; Xue Yang; Siyu Ruan; Anqi Zhou; Shanfeng Huang; Haile Ma (Journal of Food Quality)
This study aims at preparing the Maillard reaction products of protein hydrolysate from grass carp (Ctenopharyngodon idella) bone and identifying its characteristic flavour compounds. Meanwhile, bioactivities and amino acids composition of hydrolysates and its Maillard reaction products were compared with the thermal degradation reaction as one positive control. Single factor experiment was applied to optimize the enzymolysis parameters of grass carp bone protein using flavourzyme, under which the highest degree of hydrolysis (40.1%) was obtained. According to the response surface methodology, the top predicted value (70.45%) of degree of graft of Maillard reaction was obtained with initial pH of 7.07, temperature of 118.33°C, and time of 1.75 h. Moreover, the results of Maillard reaction products illustrated a significant increase in DPPH radical scavenging activity (p<0.05) compared to that of hydrolysate and its thermal degradation products, which was accompanied by the decreased ACE inhibitory activity. Besides, the umami-sweet taste amino acid ratio in free amino acids of Maillard reaction products climbed considerably compared to those of hydrolysate and its thermal degradation products, which proved that Maillard reaction is an effective way to improve the flavour taste of protein hydrolysate. The GC-MS results showed that 37, 40, and 62 kinds of volatile compounds were detected in hydrolysate, thermal degradation products, and Maillard reaction products, respectively. The Maillard reaction products contained more flavour volatile compounds of aldehydes, alcohol, ketone, pyrazine, and other compounds that contribute to pleasant aromas. These results suggested that the grass carp bone protein hydrolysate after Maillard reaction could potentially have a wide range of applications as antioxidant and flavour substances.